2015
DOI: 10.1155/2015/694023
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Carbonate in the Treatment of Graves’ Disease with ATD-Induced Hepatic Injury or Leukopenia

Abstract: Objective. GD with ATD-induced hepatic injury or leukopenia occurs frequently in clinical practice. The purpose of the present study was to observe the clinical effect of lithium carbonate on hyperthyroidism in patients with GD with hepatic injury or leukopenia. Methods. Fifty-one patients with GD with hepatic injury or leukopenia participated in the study. All patients were treated with lithium carbonate, in addition to hepatoprotective drugs or drugs that increase white blood cell count. Thyroid function, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…21 The failure of LC treatment may be related to high levels of THs, the presence of TRAB, and thyroiditis. 20 Although these factors were present in our case, the patient had a good response to LC, beta-blocker, and glucocorticoid. This observation is corroborated by data in the literature showing improvement in TH levels in patients with GD after treatment for 36 weeks with LC 500 to 750 mg/day, associated or not with glucocorticoid and/or beta-blockers.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…21 The failure of LC treatment may be related to high levels of THs, the presence of TRAB, and thyroiditis. 20 Although these factors were present in our case, the patient had a good response to LC, beta-blocker, and glucocorticoid. This observation is corroborated by data in the literature showing improvement in TH levels in patients with GD after treatment for 36 weeks with LC 500 to 750 mg/day, associated or not with glucocorticoid and/or beta-blockers.…”
Section: Discussionmentioning
confidence: 53%
“…This observation is corroborated by data in the literature showing improvement in TH levels in patients with GD after treatment for 36 weeks with LC 500 to 750 mg/day, associated or not with glucocorticoid and/or beta-blockers. 20 LC is safe to treat patients with preoperative hyperthyroidism when ATDs are contraindicated. 20 There are few cases in the literature describing the use of lithium to treat thyrotoxicosis without planning for definitive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11,24,33 We found that the addition of lithium carbonate (200 mg/day) to basal MMI treatment reduced the thyroid hormone concentration of the present patient. Because anti-thyroid effects of lithium carbonate have been reported at doses of 600 to 900 mg/day, 11,33,34 we increased her lithium carbonate dose to 800 mg/day. However, inorganic iodine and corticosteroid were simultaneously administered; therefore, we do not know whether the escalation of the dose of lithium carbonate was the key change in therapy in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean patient who was refractory to antithyroid drug treatment was successfully managed with cholestyramine [ 39 ], and serious hepatic dysfunction caused by the antithyroid drug was managed with hemodialysis [ 40 ]. The utility of potassium iodide [ 41 ] and lithium carbonate [ 42 ] as an adjuvant therapy has also been examined. Presentation of these difficult cases is vital when attempting to fill the gaps and cracks in existing knowledge and guidelines.…”
Section: Clinical Updates In Autoimmune Hyperthyroidismmentioning
confidence: 99%